COVID-19: a vascular nightmare unfolding - Yin, Qinan; Huang, Youjin; Wang, Hulin; Wang, Yin; Huang, Xuefei; Song, Yujie; Wang, Yueyuan; Han, Lizhu; Yuan, Bian (Frontiers in Immunology, 2025)
The emergence of COVID-19 has been associated with an increased risk of arteriovenous thrombosis, with immune inflammation playing a significant role in the pathogenesis of thrombosis. Numerous drug-related clinical trials have been undertaken to prevent thrombosis, and guidelines for its prevention and treatment are continuously evolving as our understanding of the disease progresses. This article provides a comprehensive review of the mechanisms underlying thrombosis in COVID-19 patients, as well as the advancements in clinical trials and guidelines for thrombosis prevention with pharmacological interventions.